Exercise induced neuropathic lower leg pain due to a tibial bone exostosis. Issue 3 (3rd July 2021) - van den Hurk, Loreen; van den Besselaar, Marijn; Scheltinga, Marc
ABSTRACT: Objectives : The differential diagnosis of chronic exercise induced lower leg pain in sporters includes compartment syndrome and medial tibial stress syndrome. However, severe discomfort may also be caused by nerve entrapment. Methods : Here we present a marathon runner who reports pain day and night in the lower leg. Deep palpation suggested the presence of a bony tumor deep in the calf musculature, and digital pressure on the soleal sling was painful and elicited paresthesias in the foot. A swab test indicated a hypo-esthetic sole of the foot. Imaging revealed the presence of a tibial exostosis that was hypothesized to narrow the soleal tunnel and irritate the tibial nerve. Results : Via a medial infragenual approach, the soleal tunnel was opened. A bony prominence was found in direct contact to the tibial nerve. Resection of the exostosis with tibial nerve neurolysis completely abolished all of his symptoms. Conclusion : An awkward lower leg discomfort that is present at night and worsens during exercise combined with altered foot sole skin sensation in the presence of a tibial bone exostosis may suggest tibial nerve neuropathy. If conservative therapies fail, resection and neurolysis is advised.